1995
DOI: 10.1007/bf00116481
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of the laboratory-based OECD earthworm toxicity test to metal-contaminated field sites

Abstract: : The effects of cadmium, copper, lead and zinc on survival, growth, cocoon production and cocoon viability of the earthworm Eisenia fetida (Savigny) were determined in three experiments. In experiment 1, worms were exposed to single metals in standard artificial soil. For experiment 2, worms were maintained in contaminated soils collected from sites at different distances from a smelting works situated at Avonmouth, south-west England. In experiment 3, worms were exposed to mixtures of metals in artificial so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
4
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(107 citation statements)
references
References 33 publications
12
86
4
5
Order By: Relevance
“…Grelle and Descamps (1998) also found that soil total Pb concentration was a better predictor of earthworm body burden than CaCl 2 -extractable Pb levels. Previous studies demonstrated that soil physicochemical properties have a significant impact on Pb uptake by E. andrei (Spurgeon and Hopkin, 1995;Peijnenburg et al, 1999;Bradham et al, 2006;Smith et al, 2012). For example, soil pH has been suggested as the most important factor for controlling the bioavailability of Pb in soil, followed by organic matter content (Thomas, 1997;Peijnenburg et al, 1999).…”
Section: The Relationship Between Biological Responses and Physicochementioning
confidence: 99%
“…Grelle and Descamps (1998) also found that soil total Pb concentration was a better predictor of earthworm body burden than CaCl 2 -extractable Pb levels. Previous studies demonstrated that soil physicochemical properties have a significant impact on Pb uptake by E. andrei (Spurgeon and Hopkin, 1995;Peijnenburg et al, 1999;Bradham et al, 2006;Smith et al, 2012). For example, soil pH has been suggested as the most important factor for controlling the bioavailability of Pb in soil, followed by organic matter content (Thomas, 1997;Peijnenburg et al, 1999).…”
Section: The Relationship Between Biological Responses and Physicochementioning
confidence: 99%
“…Cd, Co and Pb were all higher than the TCs but lower than the IC and SBs for all the sites (TDF−15 km). The effects of Cr [18,19], Cu [20,21], Ni [22] and Zn [23] on either growth or reproduction of earthworms has been reported on. These reported effects were, however, at higher metal concentrations than found in the present study, but it has to be taken into account that these studies were conducted using single metals as contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…Many other studies have reported the metal's toxicity to earthworms, tested both in artificial and field soil (Neuhauser et al, 1985;Spurgeon et al, 1994;Spurgeon and Hopkin 1995). They concluded that the toxic effects of metals were less severe in field soils (Spurgeon and Hopkin, 1995). It should be noted that simultaneous exposure to several metals can also lead to antagonistic, not necessarily to additive or synergistic effects, as observed by Khalil et al (1996).…”
Section: Earthworm Adult Survival and Growthmentioning
confidence: 99%
“…In our study, soil pH remained in the neutral to slightly alkaline range. Many other studies have reported the metal's toxicity to earthworms, tested both in artificial and field soil (Neuhauser et al, 1985;Spurgeon et al, 1994;Spurgeon and Hopkin 1995). They concluded that the toxic effects of metals were less severe in field soils (Spurgeon and Hopkin, 1995).…”
Section: Earthworm Adult Survival and Growthmentioning
confidence: 99%